Sulfonated Graphene as a Sustainable Catalyst for Environmentally Benign Preparation of Benzylidene Acetals of Carbohydrates - Rabha, Padmashri; Sharma, Anjali; Panchadhayee, Rajib (Synlett, 2023)
A clean and efficient method has been developed for the introduction of benzylidene acetals into carbohydrate derivatives catalyzed by sulfonated graphene at room temperature. Yields were excellent in each case. The catalyst can be reused several times without much decrease in reactivity.
Keywords: benzylidene acetals; carbohydrates; protecting group; graphene catalysis; solvent-free reaction; sulfonated graphene